PERBANDINGAN EFEKTIVITAS KOMBINASI OBAT ANTIDIABETIKA DENGAN METFORMIN & TANPA METFORMIN PADA PASIEN DIABETES MELITUS DENGAN GANGGUAN FUNGSI GINJAL DI RS X KOTA SURAKARTA - Ovikariani; Ramadhan , Taufiq (LPPM Universitas Awal Bros, 2025)
Metformin is the first-line therapy for type 2 diabetes mellitus; however, its use in patients with impaired renal function remains controversial. This study aimed to compare the effectiveness of combination antidiabetic therapy with and without metformin in patients with type 2 diabetes mellitus and renal impairment. A cross-sectional retrospective study was conducted using medical records of patients at Hospital X in Surakarta from January to December 2024. Patients with an estimated glomerular filtration rate below 60 mL/min/1.73 m² who received combination antidiabetic therapy for at least three months were selected through purposive sampling. Treatment effectiveness was evaluated based on the achievement of HbA1c levels below 7%. A total of 36 patients met the study criteria. The results showed no significant association between age, sex, comorbidities, or stage of chronic kidney disease and glycemic target achievement. None of the patients receiving metformin achieved the HbA1c target, while some patients in the non-metformin group did, although the difference between the two regimens was not statistically significant (p = 0.076). In conclusion, combination therapy with metformin did not demonstrate superior effectiveness compared to non-metformin combination therapy in this patient population.